Netherland - O'Neill, Joseph, 1964- (New York : Vintage Books, 2009)
In a New York City made phantasmagorical by the events of 9/11, Hans -- a banker originally from the Netherlands -- finds himself marooned among the strange occupants of the Chelsea Hotel after his English wife and son return to London. Alone and untethered, feeling lost in the country he had come to regard as home, Hans stumbles upon the vibrant New York subculture of cricket, where he revisits his lost childhood and, thanks to a friendship with a charismatic and charming Trinidadian named Chuck Ramkissoon, begins to reconnect with his life and his adopted country.--From publisher description.
Originally published in New York by Pantheon Books, 2008.
Keywords: Immigrants -- Fiction; New York (N.Y.) -- Fiction